Taxonomic notes on the genus Afghanicenus Heyrovský, 1941 (Coleoptera: Cerambycidae), with the first record of Afghanicenus nuristanicus (Heyrovský, 1936) from Pakistan - Karpiński, Lech; Das, Barsa; Barclay, Maxwell V. L. (Zootaxa, 2024)
Afghanicenus nuristanicus (Heyrovský, 1936) is hereby newly recorded from Pakistan based on a specimen collected at the beginning of the 20th century and preserved in the collection of the Natural History Museum, London. High quality colour images of the type material (a male syntype of Purpuricenus nuristanicus and a female syntype of P. nuristanicus f. bisignata) are presented for the first time. Some literature information on the genus Afghanicenus Heyrovský, 1941 is summarised, and taxonomic problems are highlighted and further discussed.